The Influence of Digital Transformation and Organizational Agility on Business Performance Mediated by Product Innovation - Bintang Narpati; Asep Hermawan; Deasy Aseanty (Greenation International Journal of Economics and Accounting, 2025)
Objective: This study aims to analyze the influence of digital transformation, organizational agility, and knowledge management on the business performance of culinary Micro, Small, and Medium Enterprises (MSMEs) in Bekasi City, with product innovation as a mediating variable, and to identify strategies for maintaining the sustainability of traditional culinary arts amidst competition from foreign food. Research Method: This study used a quantitative approach with a survey design. Data were collected through questionnaires distributed to culinary MSMEs in Bekasi City, selected due to the significant growth of its culinary sector. Data analysis was conducted using statistical methods using Structural Equation Modeling (PLS-SEM), including validity and reliability tests, and path analysis to test the direct and mediation hypotheses. Results: The results indicate that digital transformation and organizational agility have a positive and significant effect on the business performance of culinary MSMEs. Product innovation is proven to mediate the relationship between these three independent variables and business performance, strengthening the competitiveness of MSMEs in the face of globalization trends. Research Implications and Limitations: The practical implications of this research are the need for culinary MSMEs to adopt digital technology and increase organizational agility to support product innovation relevant to the modern market. Theoretical implications include strengthening the dynamic capability theory in the context of culinary MSMEs. Limitations of the research include its focus on Bekasi City, requiring adjustments to generalizations to other regions, and the limited availability of secondary data that may affect the depth of the analysis. Originality: This research provides an original contribution by integrating digital transformation and organizational agility into a single model mediated by product innovation, specifically in the context of culinary MSMEs in Bekasi City. This research also highlights the revitalization of traditional culinary arts in response to shifting consumer preferences due to globalization.